Experimental and numerical study of nanofluid flow and heat transfer over microscale forward-facing step - Kherbeet A.S.; Mohammed H.A.; Munisamy K.M.; Saidur R.; Salman B.H.; Mahbubul I.M. (Elsevier Ltd, 2023)
Experimental and numerical investigations are presented to illustrate the nanofluid flow and heat transfer characteristics over microscale forward-facing step (MFFS). The duct inlet and the step height were 400?m and 600?m respectively. All the walls are considered adiabatic except the downstream wall was exposed to a uniform heat flux boundary condition. The distilled water was utilized as a base fluid with two types of nanoparticles Al2O3 and SiO2 suspended in the base fluid. The nanoparticle volume fraction range was from 0 to 0.01 with an average nanoparticle diameter of 30nm. The experiments were conducted at a Reynolds number range from 280 to 480. The experimental and numerical results revealed that the water-SiO2 nanofluid has the highest Nusselt number, and the Nusselt number increases with the increase of volume fraction. The average friction factor of water-Al2O3 was less than of water-SiO2 mixture and pure water. The experimental results showed 30.6% enhancement in the average Nusselt number using water-SiO2 nanofluid at 1% volume fraction. The numerical results were in a good agreement with the experimental results. © 2014 Elsevier Ltd.